A synergetic control design of generator excitation and STATCOM of power systems - Adirak Kanchanaharuthai; Arsit Boonyaprapasorn (Journal of Current Science and Technology, 2014)
This paper designs a synergetic controller for an electrical power system with generator excitation and static synchronous compensator (STATCOM) to enhance transient stability and voltage regulation. With the help of synergetic control theory, the simplified nonlinear model of a power system with excitation and STATCOM can be derived and used to achieve not only power angle stability, but also frequency and voltage regulations during a large perturbation (or disturbance) on the transmission lines, such as a symmetrical three-phase short circuit fault. The simulation results show that the proposed controller can improve the system transient stability under severe disturbances and achieve power angle stability as well as frequency and voltage regulations.